KEPASTIAN HUKUM DALAM PUTUSAN MAHKAMAH KONSTITUSI TERKAIT UJI FORMIL - Ratib, Victor Albadi’u; Hedwig Adianto Mau,; Maryano, Maryano (Journal of Innovation Research and Knowledge, 2025)
Since its establishment, the Constitutional Court of Indonesia has been instrumental in upholding the supremacy of the 1945 Constitution through its constitutional review mechanism. While initially focusing on the substantive aspects of legislation, the Court has progressively extended its scrutiny to include the formal constitutionality of the lawmaking process. This study adopts a normative juridical approach, employing statutory, case, conceptual, and analytical methods. Legal materials were gathered from primary, secondary, and tertiary sources and analyzed through grammatical, systematic, and teleological interpretation. The research finds that the Constitutional Court has evolved from a moderate stanceprioritizing legal continuity—to a more assertive role in guarding procedural legitimacy, particularly through the introduction of the concept of conditional unconstitutionality. Recent jurisprudence, however, demonstrates a pragmatic approach wherein laws are annulled only if procedural violations are deemed substantial and infringe upon democratic principles such as representation and public participation. Decisions No. 27/PUU-VII/2009, No. 91/PUU-XVIII/2020, and No. 132/PUU-XXII/2024 reflect the Court’s increasing commitment to ensuring that legislative procedures align with constitutional standards. These developments reinforce the principle that procedural compliance is not merely formalistic, but essential to the legitimacy of democratic lawmaking and the realization of legal certainty in Indonesia.